THE NEW MEDIA AND TRANSFORMATION OF THE PUBLIC POLITICAL SPHERE IN GEORGIA - CHEDIA, Beka (CENTRAL ASIA AND THE CAUCASUS, 2011)
Today, when information technology is sweeping the world, it is commonly thought that the social media have essentially pushed the traditional media aside to emerge as an important factor behind public opinion. This is especially obvious in countries where the traditional media (including TV) lack pluralism and operate under the pressure of the powers that be. Georgia is one such country, where the social media serve as a lifebuoy for the public political sphere. They provide the luxury of interactive communication, while the traditional media drown the audience in unidirectional information flows. This means that the social media not merely disseminate information, they serve as a platform for political discussions (something which Georgia lacked in the past). It has become absolutely clear that people are not indifferent to political issues— this is confirmed by the heated discussions on the Internet. According to the polls conducted by the Georgian National Communications Commission (GNCC), the Georgian population prefers to watch entertainment and sports events than to ponder on political issues. This means that the country will not acquire new public-political TV and radio channels any time soon. Meanwhile, the Internet and social media are rapidly developing